Bitter taste in cassava roots correlates with cyanogenic glucoside levels - Chiwona-Karltun, L.; Brimer, L.; Kalenga Saka, J.D.; Mhone, A.R.; Mkumbira, J.; Johansson, L.; Bokanga, M.; Mahungu, N.M.; Rosling, H. (Wiley, 2004)
Cassava roots contain cyanogenic glucosides. Malawian farmers classify cultivars into two groups based on the perceived danger of eating raw roots that they associate with bitterness. In the vernacular, cultivars that produce roots with bitter taste are called vyakubaba (bitter), whereas those yielding non-bitter roots are called vyakuzizra (cool). In the scientific literature they are distinguished as ‘bitter’ or ‘sweet’. Roots from ‘bitter’ cultivars are processed prior to consumption. We studied the ability of farmers to predict the cyanogenic glucoside levels of 492 roots from the 10 most commonly grown cultivars. Twenty-eight farmers predicted the taste of each of the cultivars that they grew, and scored bitterness on a five-point scale by tasting the root tip. Thereafter cyanogenic glucosides were determined on half of the root, while a taste panel scored the taste of the other half. The mean cyanogenic glucoside level in 132 roots from ‘cool’ cultivars was 29 mg HCN eq kg−1 fresh weight (CI 25–33, range 1–123) and in 360 roots from ‘bitter’ cultivars was 153 mg HCN eq kg−1 fresh weight (CI 143–163, range 22–661). Farmers' distinction of ‘cool’ and ‘bitter’ cultivars predicts glucoside levels. The tasting of the tip of the root improved the farmers' prediction of toxicity. Scoring of bitterness by a trained taste panel showed a stronger correlation with glucoside levels (r2 = 0.67). This suggests that cyanogenic glucosides confer the bitter taste, notwithstanding the probability of additional modifying intrinsic factors.